Profile of Metacognition Skill of Students with Dependent Field Cognitive Style in Solving HOT Problems in Science - Shofiyah, N; Zannah, M; Wulandari, F E (Journal of physics. Conference series, 2021)
Metacognition is a skill that focuses on monitoring activities and self-responsibility, so students are able to organize themselves in planning, monitoring and reflecting on their learning activities. The purpose of this study is to describe the metacognition skills of VIII grade students of SMPN 3 Sidoarjo in solving HOT problems. The research subject was a student who had a dependent field cognitive style. This research is a type of qualitative research. The data was in the form of HOT test results, interview transcripts and observation results. The data is described, analyzed and tested for validity using triangulation techniques. The result of this study showed that the student who had dependent field cognitive style master the metacognition indicators of planning, monitoring and reflection in solving the C4 and C5 HOTs problems. Meanwhile, in the case of HOTS C6, subject mastered the indicators of planning and monitoring.